Complications and re-operations after Bristow-Latarjet shoulder stabilization: a systematic review - Griesser, Michael J.; Harris, Joshua D.; McCoy, Brett W.; Hussain, Waqas M.; Jones, Morgan H.; Bishop, Julie Y.; Miniaci, Anthony (Journal of shoulder and elbow surgery, 2013)
Various methods of bony stabilization, including modifications of Bristow and Latarjet procedures, are considered gold-standard treatment for recurrent anterior shoulder instability but are associated with unique complications and risk of reoperation. The purpose of this study was to identify the prevalence of these complications. We hypothesized that the Bristow-Latarjet procedure would be a successful technique for treatment of shoulder instability but associated with a risk of recurrent postoperative instability, reoperation, and other complications. A systematic review of multiple medical databases included studies reporting outcomes with complication and reoperation rates following original or modified versions of the Bristow or Latarjet shoulder stabilization surgeries. Forty-five studies were analyzed (1,904 shoulders) (all Level IV evidence). Most subjects were male (82%). The dominant shoulder was the operative shoulder in 64% of cases. Mean subject age was 25.8 years. Mean clinical follow-up was 6.8 years. Ninety percent of surgeries were done open; 9.3% were all-arthroscopic. Total complication rate was 30%. Recurrent anterior dislocation and subluxation rates were 2.9% and 5.8%, respectively. When reported, most dislocations occurred within the first year postoperatively (73%). Nearly 7% of patients required an unplanned reoperation following surgery. Osseous stabilization shoulder surgery using original or modified Bristow and Latarjet procedures has a 30% complication rate. Rates of recurrent dislocation and reoperation were 2.9% and 7%, respectively. Mild loss of external rotation is common. Reoperation rates were lower following all-arthroscopic techniques. There was a greater loss of postoperative external rotation with all-arthroscopic surgery.